Luminescent Polynuclear Zn- and Cd-Ln Square-Like Nanoclusters With a Flexible Long-Chain Schiff Base Ligand - Zhu, Ting; Yang, Xiaoping; Zheng, Xiaohui; Wang, Shiqing; Bo, Le; Wang, Chengri; Chen, Hongfen; Jiang, Dongmei; Schipper, Desmond (Frontiers in Chemistry, 2018)
Two series of Zn-Ln and Cd-Ln nanoclusters [Ln4Zn8L2(OAc)20(OH)4] (Ln = Nd (1), Yb (2) and Sm (3)) and [Ln2Cd2L2(OAc)2(OH)2(OCH3)2] (Ln = Nd (4), Yb (5) and Sm (6)) were prepared using a long-chain Schiff base ligand built around a flexible (CH2)2O(CH2)2O(CH2)2 chain. All these clusters show square-like structures. The long-chain Schiff base ligands display “linear” configurations in these clusters, and the metric dimensions of Zn-Ln and Cd-Ln clusters measure approximately 8 × 14 × 21 Å and 8 × 12 × 12 Å, respectively. The chromogenic Zn/L and Cd/L components in these clusters can act as efficient sensitizers for lanthanide luminescence. 1-6 show visible and NIR emissions.